The Influence of Organizational Culture and Career Development on Employee Performance with Job Satisfaction as an Intervening Variable - Muhammad Nepo Fauzan; Suprapto Suprapto (Dinasti International Journal of Education Management And Social Science, 2023)
This study aims to determine the influence of organizational culture and career development on employee performance with job satisfaction as an intervening variable (at Aerodrome Control Tower Unit of Perum LPPNPI Jakarta), with a sample of 140 respondents from 200 workers total population on Aerodrome Control Tower Unit Perum LPPNPI Jakarta. The data analysis method used SEM-PLS (Structural Equation Model-Partial Least Square) and was processed by Smart PLS 3.2.9. This study proves that 1.) Organizational culture positively and significantly affect employee performance; 2.) Career development positively and significantly affects employee performance; 3.) Organizational culture positively and significantly affect job satisfaction; 4.) Career development positively and significantly affects job satisfaction; 5.) Job satisfaction positively and significantly affect employee performance; 6.) Organizational culture positively and significantly affect employee performance through job satisfaction as an intervening variable; 7.) Career development positively and significantly affects employee performance through job satisfaction as an intervening variable.